THE CORRESPONDENCE BETWEEN PHONETIC TRANSCRPTION AND ORTHOGRAPHIC TRANSCRIPTION IN ENGLISH - Surono Surono (Prasasti: Journal of Linguistics, 2016)
This study entitled The Correspondence between Phonetic Transcription and Orthographic Transcription in English is intended to describe how phonetic symbols correspond to orthographic symbols (alphabets), and to find the most complex and simplest phonetic symbols and orthographic symbols (alphabets). This study belongs to descriptive qualitative type. The research object is the phonetic transcription and orthographic transcription. The data were in the forms of words and their phonetic transcription and they were gathered from two dictionaries, namely Oxford Advanced Learner’s Dictionary of Current English written by Hornby (1986) in complete version and Longman Dictionary of Contemporary English written by Longman (2001). The data were gathered by observation method followed by noting technique. Then, dividing-key-factor technique using mental ability in dividing the data was used to analyze the data. The research findings show that in English the phonetic symbols (transcription) have one-to-many correspondence with the orthographic symbols (transcription) viewed from both sides. Viewed from the phonetic symbols, there are only two symbols which have one-to-onecorrespondence, namely [æ] and [Ɔ], but viewed from the orthographic symbols, all alphabets have one-to-many correspondence. The most complex phonetic symbol referring to vowels is [i:], while the simplest one is [æ]. The most complex phonetic symbols referring to diphthongs are [iə] and [uə], while the simplest one is [au]. Finally, the most complex orthographic symbol (alphabet indicating vowels) is o, while the simplest one is e.